2020
DOI: 10.1038/s41598-020-73932-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to pitch-altered feedback is independent of one’s own voice pitch sensitivity

Abstract: Monitoring voice pitch is a fine-tuned process in daily conversations as conveying accurately the linguistic and affective cues in a given utterance depends on the precise control of phonation and intonation. This monitoring is thought to depend on whether the error is treated as self-generated or externally-generated, resulting in either a correction or inflation of errors. The present study reports on two separate paradigms of adaptation to altered feedback to explore whether participants could behave in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
(140 reference statements)
2
7
0
Order By: Relevance
“…The latent class analyses identified three subgroups in our respondents: 57% switchers, 28% opposers, and 15% followers. The distribution of the three subgroups, to a certain degree, resembled the distribution in Alemi et al (2020) , who found 47% switchers, 41% opposers, and 12% followers. The methodological differences between our study and Alemi et al (2020) lie in three aspects.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The latent class analyses identified three subgroups in our respondents: 57% switchers, 28% opposers, and 15% followers. The distribution of the three subgroups, to a certain degree, resembled the distribution in Alemi et al (2020) , who found 47% switchers, 41% opposers, and 12% followers. The methodological differences between our study and Alemi et al (2020) lie in three aspects.…”
Section: Discussionsupporting
confidence: 55%
“…The distribution of the three subgroups, to a certain degree, resembled the distribution in Alemi et al (2020) , who found 47% switchers, 41% opposers, and 12% followers. The methodological differences between our study and Alemi et al (2020) lie in three aspects. First, we examined vocal responses to sudden and short pitch shifts at a random point during vocalizations (compensation study), whereas Alemi et al (2020) examined adaptive responses to sustained pitch shifts that were applied from vocal onset to the end of vocalizations (adaptation study).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A single study using DIVA was able to replicate this relationship for simulated participant responses, with vowel formant target sizes modeled using Gaussian distributions with varying distribution variances (i.e., vowel formant acuity was inversely related to distribution variance; [ 104 ]). However, in terms of laryngeal motor control, there have been conflicting prior study observations about the relationship between auditory feedback perturbation magnitudes and corresponding vocal f o acuity, suggesting that there could be a complex relationship (or lack thereof) between generating corrective feedback for auditory feedback errors and perceiving those feedback errors [ 68 , 98 , 105 , 106 ]. Including vocal f o acuity as a variable parameter will allow for modeling intra-speaker f o acuity variability in LaDIVA, helping to interpret these recent findings.…”
Section: Discussionmentioning
confidence: 99%